Level of safety practices among welders in a developing economy in Rivers State, Nigeria - Onumbu, Chime Ishmael (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
This study investigated the safety practices among welders in developing economies in Rivers State. The descriptive cross-sectional survey research design was adopted for the study of a population of 2,718 welders in Rivers State. Taro Yamene’s formula was used to arrive at a sample size of 349. Thereafter, it was increased to 810 by the researcher through a multi-stage sampling procedure to minimize sample errors. Cronbach Alpha Coefficient test was used as a pre-test which derived the reliability of the instrument at 0.86. The instrument for data collection was the questionnaire, designed in a 4-point modified Likert scale. Percentage, mean and standard deviation were used to analyze the research question. The findings of this study showed that there was a low level of safety practices among the welders (1.95 ± 0.42) However, high levels of safety practices were found in the use of eye devices (3.99 ±0.06) and safety boots (3.03 ± 0.38). It was recommended among others that healthcare providers should not only supervise the welders' use of safety devices at work but also provide the devices to them. More mass awareness campaigns on welder safety practices should be upheld in Rivers State for better economic development.